Fraud Brainstorming Using Computer-Mediated Communication: The Effects of Brainstorming Technique and Facilitation - Lynch, Antoinette L.; Murthy, Uday S.; Engle, Terry J. (The Accounting Review, 2009)
ABSTRACT: This study experimentally investigates the effectiveness of computer-mediated brainstorming in the context of the SAS No. 99 mandated fraud brainstorming requirement. Results indicate that brainstorming effectiveness is significantly higher for teams brainstorming electronically relative to teams using traditional face-to-face brainstorming. There is no significant difference in brainstorming effectiveness between electronic interactive brainstorming and electronic nominal brainstorming. Brainstorming effectiveness is significantly higher for teams receiving content facilitation relative to teams not receiving content facilitation. The post-brainstorming fraud risk assessments are significantly higher than the pre-brainstorming assessments in all treatment conditions, indicating that the SAS No. 99 mandated brainstorming session has the intended effect. This research informs audit practice by demonstrating that computer-mediated fraud brainstorming can be more effective than face-to-face brainstorming and also by establishing the effectiveness of content facilitation for improving the quality of the fraud risk factors generated by auditors.